Role of altered esophageal intraluminal baseline impedance levels in patients with gatroesophageal reflux disease refractory to proton pump inhibitors. Issue 33 (August 2016) - Jiang, Liuqin; Ye, Bixing; Lin, Lin; Wang, Ying; Wang, Meifeng
Abstract : Abstract: Numerous studies have investigated utility of esophageal intraluminal baseline impedance levels (BILs) in gastroesophageal reflux disease (GERD). However, effect of BILs in refractory GERD (RGERD) has not been well investigated. The aim of this study is to evaluate role of BILs in RGERD patients. Total 62 subjects with refractory gastroesophageal reflux symptoms underwent 24-hour impedance-pH monitoring and gastroendoscopy. Distal BILs in acid reflux type were significantly lower than those in nonacid reflux type and functional heartburn (FH) group. Distal BILs of reflux esophagitis (RE) patients were lower than those of nonerosive reflux disease (NERD) patients, while there were no statistical significance between 2 groups. Patients with severe esophagitis had lower distal BILs than those with mild esophagitis and NERD patients, and patients with severe esophagitis in acid reflux type had the lowest distal BILs. Distal BILs were significantly negatively correlated with DeMeester score, episodes of acid reflux, and acid exposure time, but no correlated with episodes of nonacid reflux. Characteristics of BILs in RGERD patients were similar with those in GERD patients, but might be more complicated. Evaluating BILs in RGERD patients could achieve a better understanding of pathophysiology in RGERD.